O mapa conceitual como ferramenta de apoio ao ensino de representação gráfica em arquitetura - Rabel, Cezar (2015)
This paper discusses the graphical representation of education in architecture, considered in its integration with the design activity. Discusses concepts related to design in architecture, notably those linked to the character of the design process, their format from the perspective of reflection in action and the role of strategic vision in its structure and organization. Deepens concepts relating to represent in architecture in order to systematize and provide subsidies that allow the use of instruments and techniques of representation as a research tool in architecture. Asks both the design of such instruments as static and a priori as the design approach given as isolated from the space design process. Presents possibilities generated by the use of concept maps as a teaching tool and knowledge organization in the imaging teaching in architecture, it synthesizing such considerations and subsidies, as a contribution to a possible proposal for graphical representation of education in architecture